Maternal Deprivation in Rats Decreases the Expression of Interneuron Markers in the Neocortex and Hippocampus - Aksic, Milan; Poleksic, Joko; Aleksic, Dubravka; Petronijevic, Natasa; Radonjic, Nevena V.; Jakovcevski, Maja; Kapor, Slobodan; Divac, Nevena; Filipovic, Branislav R.; Jakovcevski, Igor (Frontiers in Neuroanatomy, 2021)
Early life stress has profound effects on development of the central nervous system. We exposed 9-day-old rat pups to a 24 h maternal deprivation (MD) and sacrificed them as young adults (60-day-old), with the aim to study the effects of early stress on forebrain circuitry. We estimated numbers of various immunohistochemically defined interneuron subpopulations in several neocortical regions and in the hippocampus. MD rats showed reduced numbers of parvalbumin-expressing interneurons in the CA1 region of the hippocampus and in the prefrontal cortex, compared with controls. Numbers of reelin-expressing and calretinin-expressing interneurons were also reduced in the CA1 and CA3 hippocampal areas, but unaltered in the neocortex of MD rats. The number of calbinin-expressing interneurons in the neocortex was similar in the MD rats compared with controls. We analyzed cell death in 15-days-old rats after MD and found no difference compared to control rats. Thus, our results more likely reflect the downregulation of markers than the actual loss of interneurons. To investigate synaptic activity in the hippocampus we immunostained for glutamatergic and inhibitory vesicular transporters. The number of inhibitory synapses was decreased in the CA1 and CA3 regions of the hippocampus in MD rats, with normal number of excitatory synapses. Our results indicate complex, cell type-specific and region-specific alterations in the inhibitory circuitry induced by maternal deprivation. Such alterations may underlie symptoms of MD at the behavioral level, and possibly contribute to mechanisms by which early life stress causes neuropsychiatric disorders, such as schizophrenia.